Conceptual approaches to definition of the category «management сitizens’ savings» - Yu. V. Indychenko (Управление)
In modern conditions, of great importance is the concept of «saving citizens» and their impact on the economic situation in the country, which largely depends on the correctness of their management. Savings are a source of financial wealth of citizens, which is manifested not only in monetary form, but also in tangible and intangible assets. The article reveals conceptual approaches to the definition of categories of «citizens’ savings» and «management». It has noted that in most scientific sources savings are considered from the point of view of the individual, but it does not take into account the importance of savings in the economic growth of the country. On the base of the identified approaches, the author’s definition of the category of «citizens’ savings» has given. Systematization of theoretical aspects of various sources of domestic and foreign literature, made it clear that there is no definition of the category «management of savings of citizens». On the base of the generalized material the author’s definition «management of savings of citizens» has given. Groups of forms of savings have defined. The results of the study of the dynamics of deposits of the population in rubles and foreign currency in the period from 2014-2017 have presented. It has revealed that the population form their savings in any conditions, regardless of the economic, political and social situation in the country. This formation of savings is more dependent on the needs of the population, which leads to changes in the volume, forms and types of savings, depending on the motivation and the environment. It has noticed that the savings of citizens are the most important investment potential of the country and an additional non-inflationary source of funds for the economy.